(3QSGdI fMh YOe aSN GdELGQI HehJ eDLQgGs - (3eMeO Hf HjQe GdKGfjs
(3ChdgG (B:s
(3jG eXgQ TeS GdJMbjb HYO ESJfGQgG gPG JMbjb GdcdGe s
(3BNQgG (B:s
(3hef TQWg KHhJg HZjQ GdbjGS s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdESdGejs